2020
DOI: 10.1590/pboci.2020.134
|View full text |Cite
|
Sign up to set email alerts
|

Do Parents’ Oral Health Literacy Levels Influence Their Response to Interventions to Improve Their Knowledge of Traumatic Dental Injuries?

Abstract: To measure the influence of oral health literacy (OHL) level in the improvement of knowledge about traumatic dental injuries (TDI) after an educational intervention. Material and Methods: A total of 257 parents of children aged 0-12 years had their OHL level evaluated (BREALD-30). A leaflet with information about how to respond to TDI Emergency was developed and delivered to the parents. A questionnaire about attitudes towards TDI was administered before (TDIQ1) and after (TDIQ2) parents read the educational l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…15 In this study, higher BREALD-30 scores were associated with a higher number of correct answers even after controlling for socio-economic and demographic factors. 15 Other studies found that higher levels of parental OHL were associated with better nonclinical outcomes, such as behavior and knowledge regarding night time bottle feeding, the use of fluoride, 23 sugar intake and dental hygiene habits in children. for children demonstrated that individuals with higher OHL levels evaluated using the BREALD-30 were more likely to retain the information 4 weeks after the intervention compared with those with low OHL.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…15 In this study, higher BREALD-30 scores were associated with a higher number of correct answers even after controlling for socio-economic and demographic factors. 15 Other studies found that higher levels of parental OHL were associated with better nonclinical outcomes, such as behavior and knowledge regarding night time bottle feeding, the use of fluoride, 23 sugar intake and dental hygiene habits in children. for children demonstrated that individuals with higher OHL levels evaluated using the BREALD-30 were more likely to retain the information 4 weeks after the intervention compared with those with low OHL.…”
Section: Discussionmentioning
confidence: 45%
“…The results of this study revealed that participants with high OHL reported a better comprehension of the information contained on the IL and felt more capable of executing the tasks proposed in the leaflet compared with those with lower OHL. To the best of the authors' knowledge, only one previous study, which had a cross‐sectional design, has evaluated the effect of parental OHL level using the BREALD‐30 on knowledge regarding the management of traumatic dental injuries immediately after the reading of an information leaflet 15 . In this study, higher BREALD‐30 scores were associated with a higher number of correct answers even after controlling for socio‐economic and demographic factors 15 .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations